The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1093/nar/gkg436
|View full text |Cite
|
Sign up to set email alerts
|

Effect of DNA target sequence on triplex formation by oligo-2'-deoxy- and 2'-O-methylribonucleotides

Abstract: The interactions of pyrimidine deoxyribo- or 2'-O-methylribo-psoralen-conjugated, triplex-forming oligonucleotides, psTFOs, with a 17-bp env-DNA whose purine tract is 5'-AGAGAGAAAAAAGAG-3', or an 18-bp gag-DNA whose purine tract is 5'-AGG GGGAAAGAAAAAA-3', were studied over the pH range 6.0-7.5. The stability of the triplex formed by a deoxy-env-psTFO containing 5-methylcytosines and thymines decreased with increasing pH (T(m) = 56 degrees C at pH 6.0; 27 degrees C at pH 7.5). Replacement of 5-methylcytosines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
2
4
0
Order By: Relevance
“…These data are consistent with our previous results for the serum stability of a methylphosphonate-derivatized hairpin oligo-2′-O-methylribonucleotide (4) and with oligodeoxyribonucleotides having a 3′-terminal methylphosphonate linkage (15). The combined results show that methylphosphonate linkages located in the 3′-terminal portion of the oligomer can impart considerable protection against degradation by 3′-exonuclease activity found in mammalian sera.…”
Section: T H I S C O N T E N T Isupporting
confidence: 92%
“…These data are consistent with our previous results for the serum stability of a methylphosphonate-derivatized hairpin oligo-2′-O-methylribonucleotide (4) and with oligodeoxyribonucleotides having a 3′-terminal methylphosphonate linkage (15). The combined results show that methylphosphonate linkages located in the 3′-terminal portion of the oligomer can impart considerable protection against degradation by 3′-exonuclease activity found in mammalian sera.…”
Section: T H I S C O N T E N T Isupporting
confidence: 92%
“…While TFO RNA-C2 had a K d that was not significantly different from that of TFO DNA-C2, a modest reduction in K d was observed for TFO RNA-C6, suggesting that the 6-carbon linker further stabilizes binding by allowing better psoralen intercalation, or less likely through direct interactions with the triplex structure, consistent with observations in DNA TFOs [19]. This lack of dramatic enhancement in binding affinity of RNA third strands binding to DNA duplexes has also been observed previously by Han and Dervan [20] and may be due to the RNA TFO's lack of the C-5 methyl group in uridine which likely enhances base stacking and triplex stability [13, 18, 21, 22]. …”
Section: Resultssupporting
confidence: 80%
“…It has been shown that cyanide is an extremely strong ligand for platinum and that adding cyanide to a Pt-G adduct will displace the platinum from guanine (46-50). The t1d-4R , t2d-4Y , and t3d-4Y adducts were isolated from the gel and were treated with 200 mM sodium cyanide.…”
Section: Resultsmentioning
confidence: 99%